If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3y + -4) + -1(2y + 3) = 0 Reorder the terms: 4(-4 + 3y) + -1(2y + 3) = 0 (-4 * 4 + 3y * 4) + -1(2y + 3) = 0 (-16 + 12y) + -1(2y + 3) = 0 Reorder the terms: -16 + 12y + -1(3 + 2y) = 0 -16 + 12y + (3 * -1 + 2y * -1) = 0 -16 + 12y + (-3 + -2y) = 0 Reorder the terms: -16 + -3 + 12y + -2y = 0 Combine like terms: -16 + -3 = -19 -19 + 12y + -2y = 0 Combine like terms: 12y + -2y = 10y -19 + 10y = 0 Solving -19 + 10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 10y = 0 + 19 Combine like terms: -19 + 19 = 0 0 + 10y = 0 + 19 10y = 0 + 19 Combine like terms: 0 + 19 = 19 10y = 19 Divide each side by '10'. y = 1.9 Simplifying y = 1.9
| 6-9y=33 | | 7-2v=-9v | | 5/8y=x | | x^2+12x+35=35 | | (-x^2-50x-625)/(-3x-75) | | 7-4y=15 | | bp=4a-ap | | -143=-1x | | 5/6d=11/18 | | 2(x+1)=46 | | 4(p+2)-2(1-p)-4=0 | | m^2+5m-126=0 | | 5=5(u+4)-8u | | -8=x+11over-2 | | log(2k-4)=1+logk | | 15n^3+16n^2-7n=0 | | 12x+5y=-105 | | 5z-(z-18)=6-(z+15) | | 2(2/.5l/l)=40 | | -12+6=-2(x+5) | | 2(2/.5l/l | | 2(5x+4)-6= | | (5-3i)+(-7-2i)=0 | | 18+4=723214 | | -6(2t+3)=-78 | | (b-6)(b-4)=0 | | 3r^2-12r-135=0 | | 3(10x)+50=390 | | -12m=4(5m+8) | | b/-13=-4 | | 15=x+2y | | -10(s+5)=-24 |